Pengaruh Burnout Terhadap Prokrastinasi Akademik Pada Mahasiswa Yang Bekerja - Ayu Kholifah Sari; Melani Aprianti (Merpsy Journal, 2022)
The aim of the study was to examine the effect of burnout on academic procrastination in working students.  Using a descriptive quantitative design method with linear regression approach. Data collection using questionnaire google form.  The sampling technique was non-probability sampling using the accidental sampling method.  The research subjects obtained 203 respondents who works while studying at X University, Jakarta. The result, there is a significant effect between burnout and academic procrastination.  Burnout can predict academic procrastination of 15%.  Then, the burnout and academic procrastination categories are the moderate level.